Unveiling the Potential of Therapeutic Mesenchymal Stem Cells in Cancer Treatment - Mallu, Maheswara Reddy (Asian Journal of Pharmaceutics (AJP), 2023)
Recent studies have suggested that mesenchymal stem cells (MSC) can migrate to tumor-specific regions and stem cell-based therapies have potential in treating several cancers. Such cells are genetically modified to express certain pro-apoptotic factors, pro-drugs, anti-proliferative agents, therapeutic proteins, and anti-angiogenic agents at the tumor sites. It is also evident that new modalities of cancer therapies are needed immediately which would push this research to the clinic and render MSCs as potential vectors for targeted therapy. The current review focuses on different sources of MSC used against tumors, the interactions and behavior of MSCs in the tumor microenvironment, and the usage of MSC as delivery vectors.